Attention-based Transformer-LSTM architecture for early diagnosis and staging of early-stage Parkinson’s disease using fNIRS data - Wang, Huan; Wang, Hujun; Qie, Shuyan; Wang, Congxiao; Li, Nan; Wang, Hanming (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is a progressive neurodegenerative disorder requiring early diagnosis and accurate staging for optimal treatment outcomes. Traditional clinical assessments have limitations in objectivity and reproducibility.ObjectiveTo develop and validate an Attention-based Transformer-LSTM hybrid deep learning model (ATLAS-PD) for classifying early-stage PD patients (H&Y stages 1–2) and healthy controls using functional near-infrared spectroscopy (fNIRS) data.MethodsThis cross-sectional study enrolled 240 participants: 80 healthy controls, 80 H&Y stage 1 PD patients, and 80 H&Y stage 2 PD patients. fNIRS data were collected during a pegboard task using a 22-channel system covering prefrontal cortex regions. To address task-specific bias, a pilot complementary gait imagery task was performed on a subset of 60 participants (20 per group), with additional ROC AUC analysis. The ATLAS-PD model was compared with traditional machine learning algorithms including Support Vector Machine, Random Forest, K-Nearest Neighbors, and Back-Propagation Neural Network. McNemar’s test and bootstrap resampling were conducted to assess superiority. Interpretability analysis was conducted using permutation importance to quantify channel contributions, with regional aggregation and channel ranking to identify neurophysiologically relevant patterns. Additionally, t-SNE (t-distributed Stochastic Neighbor Embedding) dimensionality reduction was applied to visualize the feature space clustering.ResultsThe ATLAS-PD model achieved an accuracy of 88.9% (95% CI: 0.808–0.970), demonstrating superior robustness and generalization compared to traditional approaches. While SVM showed higher accuracy (92.6, 95% CI: 0.869–0.983) on the test set, it exhibited significant performance degradation under noise conditions (accuracy dropped to 45.2% at σ = 0.3). ATLAS-PD maintained 80.09% accuracy at the same noise level, indicating superior clinical applicability. The model achieved AUC values of 0.99, 0.78, and 0.88 for healthy controls, H&Y stage 1, and H&Y stage 2 groups, respectively. For the gait imagery task, macro-average AUC was 0.723, confirming model robustness across tasks. Statistical tests confirmed ATLAS-PD significantly outperformed baselines (p < 0.05). Interpretability analysis using permutation importance and attention weight visualization revealed the model primarily utilizes bilateral frontal polar cortex signals, with channels CH01, CH04, CH05, and CH08 showing highest importance scores. t-SNE visualizations further demonstrated distinct clustering of healthy controls from PD groups, with partial overlap between H&Y stages 1 and 2, reflecting the disease continuum.ConclusionATLAS-PD provides an objective, non-invasive tool for early PD diagnosis and staging in H&Y stages 1–2. The inclusion of complementary tasks and statistical validations enhances its clinical applicability. Future studies should validate the model’s performance in more advanced PD stages to enhance clinical applicability.